2012
DOI: 10.1007/s11695-012-0683-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of HOMA2-IR and HbA1c with Algorithms Derived from Bioimpedance and Spectrophotometric Devices

Abstract: The results of this study in Brazilian subjects with obesity suggest that ES complex algorithms will be useful in large-scale screening studies to predict insulin resistance, metabolic syndrome, and HbA1c >6.5%. Additional studies are needed to confirm these correlations in non-obese subjects and in other ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The sample size was calculated based on a study related to the EIS system. 6 , 8 , 10 Stata Software, Version 12.0 was used to calculate sample size, and one-sample comparison of proportions to hypothesized values in which the sensitivity of EIS was determined to be 90%. Therefore, based on the two-sided test, 5% α error and 90% power with 30% estimated prevalence of disease, 6 , 11 , 12 the number of patients needed for the study was calculated to be 117.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was calculated based on a study related to the EIS system. 6 , 8 , 10 Stata Software, Version 12.0 was used to calculate sample size, and one-sample comparison of proportions to hypothesized values in which the sensitivity of EIS was determined to be 90%. Therefore, based on the two-sided test, 5% α error and 90% power with 30% estimated prevalence of disease, 6 , 11 , 12 the number of patients needed for the study was calculated to be 117.…”
Section: Methodsmentioning
confidence: 99%
“…Electrical stimulation does act as a predictive tool for early signs of autonomic nervous system dysfunction among people with diabetes by measuring their sweat response and constitutes a modality that can be used in any physical therapy practice providing an inexpensive method to assess endothelial impairment. In addition, the study of Adami et al 8 showed that the homeostasis model assessment of insulin resistance (HOMA2-IR), HbA1c and plasma glucose level highly correlated to the algorithms derived from bio-impedance and spectrophotometric devices. However, no studies have reported the association between electro interstitial scan measured by this device and metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%